The Role of Internal Affairs Bodies in Ensuring Economic Security of Russia through the Prism of Combating Criminalization of Financial and Economic Activities of Commercial Organizations - A. V. Kudryavtsev (Управленческое консультирование)
In the article, the role of law-enforcement bodies in ensuring economic security of Russia by counteraction of criminalization of financial and economic activity of the commercial organizations is considered. Features of law-enforcement bodies in this direction are considered; their role in comparison with other law enforcement agencies is estimated. The attention to interdependence of the concepts “economic activity” and “financial and economic activity” of the commercial organizations and to a role of law-enforcement bodies in the economic policy pursued by the state is paid.